Root & Ritual : timeless ways to reconnect to land, lineage, community, and the self - Piastrelli, Becca (Boulder, CO : Sounds True, 2021)
"Root and Ritual takes knowledge of ancestral traditions and uses it as a doorway to help women reconnect with their own deeply intertwined roots that go back thousands of years as a relevant and critical way of thriving in the modern world. It offers deeply seeded truths to liberate them from the ways of being that aren't helping them thrive, as well as recipes, rituals, and instructions for their journey to feeling rooted and connected. This book also seeks to support the reader in integrating these practices in a progressive, and socially conscious way"--.
Keywords: Women -- Religious life; Women -- Psychology